Neurological Disease and Marriage - Mehmet Önger; Tuba Aydın (Sakarya Tıp Dergisi, 2020)
Marriage affects people's happiness and lifetime. Researches support the idea that married people are more healthier and happier and they have longevity than other people (single, divorced and widowed). In the world, incidence of neurological diseases increase day by day. They affects patients, their families and societies. However, marital status, marital relationship, and spouses situation affect patient's acceptance to and cope with illness. In neurological diseases such as Amyotrophic lateral sclerosis (ALS), Multiple Sclerosis (MS), Alzheimer Disease (AD), Parkinson's Disease (PD) and stroke patients, married patients are more healthier and have long life span than other patients. Then, in married patients, diseases such as MS and epilepsy can be risk factor to divorce or negatively affects their spouses or marital relationship. In the study, we aimed to examine the relation between neurological diseases and marital status, divorce, spouses' situation and marital relationship.